Leadership Traits and Administrative Behaviors Fostering Collective Effi-cacy and Satisfactory Performance among Teachers in Elementary Schools - Caparros, Morena Ann B. (Future Science / FSH-PH Publications, 2025)
This study aimed to determine the leadership skills and ad-ministrative behaviors fostering collective efficacy and satisfac-tory performance among teachers in elementary schools of Bay District, Division of Laguna. It employed the descriptive study endeavored as research method and the main technique of the study. As to the profile of school administrators, majority were 36 years old and above, more than half were female, nearly eighty percent were married, a bigger number were Bachelor's Degree with MA units, a little more than one-half occupied Teacher 1 position, and a great majority of them had served 6 to 10 years. Looking on the aspect of leadership traits the school admin-istrators were highly manifested in all areas such as effective communicators, accountable and responsible, long-term think-ers, self-motivated, confident, people oriented and emotionally stable.In terms of administrative behaviors, the school administra-tors were also found much effective in all areas such as caring and supportive, positive thinking, humility. trustworthy and empowerment. Parallel studies maybe conducted by examining other as-pects and nature of variables related to leadership skills and administrative behavior so that further assessments on the reli-ability and validity of the data in this research could be ascer-tained. It involved 300 respondents.In order to validate their assessment from the survey in-strument, the analysis and interpretation of the data gathered were facilitated by frequency counts, percentage, mean, stand-ard deviation, Pearson r and mediating variables. The study found out that there is no significant relationship between the school heads’ profile and the leadership traits and collective efficacy and school performance outcome. However, there is a significant relationship between the leadership traits, administrative behaviors, collective efficacy and performance outcome.